Modern Approach to Organization of Digital Electronics Classes - Mikenin, A. E.; Prokurat, G. A.; Krasikov, D. A.; Hachatryan, D. V. (Systems of Signals Generating and Processing in the Field of on Board Communications (Online), 2025)
Modern methods of teaching digital electronics rely on computer modeling which often leads to misunderstanding of some core design principles by students. This article is devoted to organizing classes in digital electronics using breadboard modelling for more evident explanation of main digital circuit development concepts. The article describes the method of organizing a physical model, its internal structure, and operating principle, which is proposed for implementation and subsequent use in laboratory practical for the course "Digital Circuitry." This model serves as a way to demonstrate to students the fundamental rules of Boolean algebra in practice, as well as an opportunity to assemble various basic digital circuits whose operation is based on the same rules.